Knockdown of CDK2AP1 by RNA interference inhibits cell growth and tumorigenesis of human glioma. (July 2014) - Xu, Yonggang; Wang, Jie; Fu, Songbin; Wang, Zhi
Abstract : Previous reports support the role of cyclin-dependent kinase 2-associated protein 1 (CDK2AP1) as a tumor suppressor that functions as a key player in cell cycle regulation. Although the misadjustment of CDK2AP1 has been revealed in several types of human malignancies, the functional role of CDK2AP1 in human glioma remains unknown. The present study was undertaken to investigate the effects of CDK2AP1 knockdown by RNA interference (RNAi) on glioma cell growth and tumorigenesis. We employed lentivirus-mediated RNAi to down-regulate CDK2AP1 expression in U251 and U373 cells. Knockdown of CDK2AP1 resulted in a significant reduction in U251 and U373 cell proliferation, as determined by MTT and colony formation assays. Cell cycle analysis showed CDK2AP1 silencing caused U251 cells arrest in G0/G1 phase, especially in the sub-G1 phase representing apoptotic cells. In vivo tumorigenesis was assessed using xenograft formation and CDK2AP1 depletion remarkably inhibited glioma growth and tumorigenesis. Taken together, these results suggest that CDK2AP1 siRNA may have an anti-tumorigenic effect on human glioma.